2012
DOI: 10.1016/j.ejphar.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant-like effect of Hedyosmum brasiliense and its sesquiterpene lactone, podoandin in mice: Evidence for the involvement of adrenergic, dopaminergic and serotonergic systems

Abstract: We have recently shown that the ethanol extract of the leaves of Hedyosmum brasiliense exhibits an antidepressant-like effect in the tail suspension and forced swimming tests in mice. The present study investigates the mechanisms involved in the antidepressant-like effect of H. brasiliense extract, together with the antidepressant potential of podoandin, an isolated sesquiterpenoid. H. brasiliense (50mg/kg, i.p.) and podoandin (10mg/kg, i.p.) decreased the immobility time in the forced swimming test, without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…It has also been reported that AMPT pretreated mice demolished the antidepressant activity of bupropion (a non-selective noradrenaline and dopamine reuptake inhibitor) in the TST ( Kwon et al, 2010 ). Moreover, several studies elucidated the involvement of α 1 , and α 2 - adrenoceptors in the antidepressant-like effect of drugs in animal behavioral models of depression ( Machado et al, 2009 ; Capra et al, 2010 ; Goncalves et al, 2012 ; Zeni et al, 2013 ). Evidence suggested that the brain α 1 -adrenoceptors were desensitized in the depressed patients and that the activation of α 1 - adrenoceptors restored the normal mood ( Stone et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that AMPT pretreated mice demolished the antidepressant activity of bupropion (a non-selective noradrenaline and dopamine reuptake inhibitor) in the TST ( Kwon et al, 2010 ). Moreover, several studies elucidated the involvement of α 1 , and α 2 - adrenoceptors in the antidepressant-like effect of drugs in animal behavioral models of depression ( Machado et al, 2009 ; Capra et al, 2010 ; Goncalves et al, 2012 ; Zeni et al, 2013 ). Evidence suggested that the brain α 1 -adrenoceptors were desensitized in the depressed patients and that the activation of α 1 - adrenoceptors restored the normal mood ( Stone et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the research on imidazoles as antineuropathic agents is quite active. A lot of imidazoles have been demonstrated to possess good biological activities toward some neuropathic‐relative diseases such as epilepsy, AD, Parkinson's disease, schizophrenia, dementia, anxiety, and depression . The structures of imidazole‐based antineuropathic compounds are shown in Figure .…”
Section: Imidazoles As Antineuropathic Agentsmentioning
confidence: 99%
“…Its leaves have been used in folk medicine to treat migraine, ovarium dysfunction, foot fungi, rheumatism, stomach pain, and as a diuretic [ 1 , 2 ]. Chemical and pharmacological studies with the aerial parts of H. brasiliense indicated analgesic, anxiolytic, antidepressive, and aphrodisiac effects for the crude extracts and for some isolated sesquiterpene lactones [ 11 , 12 , 13 , 14 , 15 , 16 ]. There are also some reports on the antimicrobial activity for the ethanol extract [ 17 ] and the essential oils [ 18 , 19 ], however none of them could attribute the observed bioactivity to a specific compound.…”
Section: Introductionmentioning
confidence: 99%